Barriers to Viral Suppression Among Female Sex Workers: Role of Structural and Intimate Partner Dynamics - Duff, Putu (J Acquir Immune Defic Syndr, 2016)
OBJECTIVE: Despite global evidence that sex workers (SWs) are disproportionately impacted by HIV, data on HIV treatment outcomes among SWs living with HIV remains sparse. This study examined the correlates of undetectable plasma viral load (pVL) among street- and off-street SWs living with HIV and on antiretroviral therapy (ART) in Metro Vancouver, Canada. METHODS: Analyses drew on data (2010–2014) from a longitudinal cohort of SWs (An Evaluation of Sex Workers Health Access) and confidential linkages with the Drug Treatment Program (DTP) data on ART dispensation and outcomes. Bivariate and multivariable generalized linear mixed effects models (GLMM) were used to identify longitudinal correlates of undetectable pVL (<50 copies/ml). RESULTS: Of the 72 SWs living with HIV who had ever used ART, 38.9% had an undetectable pVL at baseline. While 84.7% had undetectable pVL at least once over the study period, 18.1% exhibited sustained undetectable pVL. In multivariable GLMM analyses, ≥95% pharmacy refill adherence (Adjusted Odds Ratio (AOR)=4.21; 95% Confidence Interval (CI) 2.16–8.19), length of time since diagnosis (AOR=1.06; 95%CI 1.00–1.13) were positively correlated with undetectable pVL. Having an intimate male partner (AOR=0.35; 95%CI 0.16–0.78) and homelessness were negatively correlated with undetectable pVL (AOR=0.22; 95%CI 0.10–0.47). DISCUSSION/CONCLUSIONS: There is a need to more closely consider the social and structural contexts which shape SWs’ experiences on ART and impact treatment outcomes, including the gendered power dynamics within intimate partnerships. Future research on HIV care among SWs is urgently needed, alongside structural and community-led interventions to support SWs’ access to and retention in care.